Death‑in‑Prison Sentences: Overutilized and Underscrutinized - Henry, Jessica S. (Life without parole: America's new death penalty?, 2012)
"Is life without parole the perfect compromise to the death penalty? Or is it as ethically fraught as capital punishment? This comprehensive, interdisciplinary anthology treats life without parole as "the new death penalty." Editors Charles J. Ogletree, Jr. and Austin Sarat bring together original work by prominent scholars in an effort to better understand the growth of life without parole and its social, cultural, political, and legal meanings. What justifies the turn to life imprisonment? How should we understand the fact that this penalty is used disproportionately against racial minorities? What are the most promising avenues for limiting, reforming, or eliminating life without parole sentences in the United States? Contributors explore the structure of life without parole sentences and the impact they have on prisoners, where the penalty fits in modern theories of punishment, and prospects for (as well as challenges to) reform"-- Provided by publisher.